PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MELALUI PENDEKATAN SCIENTIFIC APPROACH BERBANTUAN PUZZLE JIGZAW - Sulistyawati, Hermin; Lestari; Eko Wahyuni, Dwi; Sudarmiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' creative thinking skills through the use of the Scientific Approach assisted by jigsaw puzzles. The method used is Classroom Action Research (CAR) which is implemented in two cycles, including the planning stage, action implementation, observation, and reflection. The research subjects are students at one level of education. Data collection techniques are carried out through observation and documentation. The results of the study indicate that the use of the Scientific Approach assisted by jigsaw puzzles can improve students' creative thinking skills, as indicated by an increase in creativity indicators in each cycle. Thus, this approach is considered effective for application in learning.